Sc(III) Complexes of 1,4,7-Triazacyclononane-1,4,7-triacetic Acid and Its Monoamides - Kubinec, Jan; Koucký, Filip; Svítok, Adam; Faltejsek, Jan; Kotek, Jan; Kubíček, Vojtěch; Hermann, Petr (Inorganic chemistry, 2025)
Scandium(III) complexes with H3nota and its N-ethyl (H2L1) and N,N-diethyl (H2L2) monoamides were studied in the solid state and solution. Potentiometric measurements showed high stabilities of the binary ScIII complexes with the ligands (log K[Sc(L)] = 19.50, 16.64, and 17.94 for H3nota, H2L1 and H2L,2 respectively) and weak coordination of the second ligand molecule under the ligand excess. The chemical model was confirmed by 45Sc NMR. Multinuclear NMR spectroscopy was used to study the ternary ScIII-ligand-oxalate systems. The results showed the presence of species with 2:1 and 1:1 [Sc(L)]-to-oxalate stoichiometry. Ternary complexes with the nota-monoamides form two isomers differing in the position of oxalate versus amide pendant arm. In the solid state, the [Sc(L)] complexes form oligomers interconnected through ligand carboxylate groups. Crystallization from solutions containing H2O2 or oxalate anions yielded ternary complexes. In all binary and ternary complexes, the ScIII ion is octacoordinated with the N3O4O1 coordination mode. All of the carboxylate groups of the ligands are coordinated in the O4-plane. The apical position is occupied by an oxygen atom of water, peroxide, or carboxylate anion. The apical Sc-O bonds are usually longer compared to those of the oxygen atoms forming the O4-plane.